ESSENTIAL STAGES FOR ENHANCING LEXICAL SKILLS IN ENGLISH COURSES AT NON-PHILOLOGICAL HIGHER EDUCATION INSTITUTIONS THROUGH CASE STUDIES - Shohsanam , Tohirova (Journal of Social Sciences, 2024)
General conclusions are given about the use of modern teaching methods, their positive impact on the professional development of students, as well as the importance of modern technologies in teaching English today. This article presents a methodology for teaching English for specific purposes using case-study technology. Relevant examples from the specialized literature on this method are given, and special attention is paid to the positive impact of problem-based learning technology on the educational process. Especially in the areas of energy education, when training sessions are organized using problem-based learning technology, we see the development of students’ lexical base and improvement of language skills. The importance of case-study technology in teaching English in non-philological institutions and the advantages of this approach in language learning by students discussed.